Complementarity and Custom in Wage Contract Violation - Earle, John S; Sabirianova Peter, Klara (The Review of Economics and Statistics, 2009)
We present and estimate a model with strategic complementarities in firms' choices of on-time or delayed wage payment. Linked employer-employee panel data from Russia facilitate identification of the endogenous interactions through fixed effects for firms, workers, and local labor markets, and instrumental variables based on policy interventions. The estimated reaction function displays strongly positive neighborhood effects, and the estimated feedback loops—worker quits, effort, strikes, and legal penalties—imply that costs of wage delays are attenuated by neighborhood arrears. We also study a nonlinear case with two stable symmetric equilibria: a punctual payment and a late payment equilibrium.